In vitro comparison of two electromagnetic shockwave generators: low-pressure wide focus vs high-pressure small focus: impact on initial stone fragmentation and final stone comminution - Rassweiler, Jens; Rieker, Philip; Pecha, Rainer; Dressel, Martin; Rassweiler-Seyfried, Marie-Claire (Journal of endourology, 2022)
Context: Recently developed concepts for higher efficacy extracorporeal shockwave lithotripsy with low-pressure wide focus systems resulting in finer fragmentation of the calculi. - Objective: To compare two different electromagnetic shockwave sources (low-pressure wide focus [Xinin Lithotripter, XL] vs high-pressure small focus [Siemens Lithoskop, SL]) by sound field measurements and in vitro fragmentation. - Evidence Acquisition: The CS-2012A XX-ES lithotripter (self-focusing electromagnetic shockwave generator with concave spherical curved electrical coil; XL) was compared to the (SL) (electromagnetic generator with a flat electric coil with an acoustical lens). Different sound field measurements were performed using a fiber-optic hydrophone. Measurements at three different power settings (XL: 8.0, 9.3, and 10.3 kV and SL: Level 1, 5, and 8). Ten AST stones and 15 BegoStones (9.3 kV, Level 3) with a frequency of 90/minute (SL) and 20/minute (XL). Number of impulses to the first crack and for complete stone comminution (residual fragments <2 mm) was documented. - Results: The median number of shockwaves for the first crack in AST stones with the XL was 12 (10-14) and 7 with the SL (6-9). Complete disintegration was accomplished after 815 (782-824) shockwaves with XL and 702 (688-712) with SL. The difference was not statistically significant. The median number of shockwaves to produce the first crack in BegoStones was 524 (504-542) with XL and only 151 (137-161) with SL. Numbers of shockwaves for complete disintegration did not differ significantly (XL: 2518 vs SL: 2287). Using a wide focus with low pressure shows more homogeneous disintegration. - Conclusion: Two stone models showed significant differences regarding form and time of the initial fragmentation. Impulses for stone comminution did not differ significantly. The advantages of a low-pressure wide-focus system include minimal trauma and a homogeneous fragment size but is more time consuming. High-pressure small-focus systems are clinically effective.
Gesehen am 24.04.2024